Indications, risk of lower airway infection, and complications to pediatric tracheotomy: report from a tertiary referral center. (3rd August 2017) - Grønhøj, Christian; Charabi, Birgitte; Buchwald, Christian von; Hjuler, Thomas
Abstract: Background: Although pediatric tracheotomy is potentially life-saving, the procedure is associated with high risk of complications, and indications have changed the last decade. We report indications, complications, and lower airway infections (LAIs) to pediatric tracheotomy performed at a tertiary referral center. Methods: We identified all children (<18 years) who underwent tracheotomy at our institution during 2008–2015. A review of hospital records was performed to extract data on indication of the procedure, complications, and information on pre- and postoperative LAI. Results: At a median age of 8 years (range: 4 months to 17 years), a total of 69 tracheotomies were performed. Neuromuscular disease ( n = 21) was the most common cause for tracheotomy. The postoperative complication rate was 22%; early complications (<30 days) occurred in four patients, and nine patients encountered late complications such as wound granulation and tracheocutaneous fistula. Children without LAI prior to tracheotomy were at increased risk of LAI from the initial 30-days following surgery (OR: 2.91, 95% CI: 1.17–7.21; p = .02). Fifty-three percent (10/19) of all LAIs following tracheotomy were caused by Staphylococcus aureus ( p < .01). Conclusions: Pediatric tracheotomy was associated with considerable rates of minor early and late complications and high risk of short-term LAI. The main cause leading to tracheotomy was neuromuscular disease.